47. OUTCOMES OF PERIPHERAL VASCULAR INTERVENTIONS IN PATIENTS WITH LOWER EXTREMITY ARTERY DISEASE (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the efficacy, short- term results of percutaneous transluminal angioplasty (PTA) in patients with symptomatic lower extremity artery disease.Methods: From June to December 2020, the cross sectional, descriptive study was carried out on 30 patients with lower limb artery disease, treated by PTA in Cardiovascular and Thoracic Department, Thong Nhat hospital. All patients were evaluated by clinical symptoms, ankle- brachial index and lesion characteristic before and after the intervention to determine the initial success.Results: Majority of lesions belong to TASC II C and D (79%). The artery treated with angioplasty were aortoiliac (68,4%), femeropopliteal (44,7%) and below-knee artery (42,1%). Balloon angioplasty and stent placement were in 24 patients (63%) and balloon angioplasty in 14 patients (27%). The ankle- brachial index before and after the intervention respectively 0,35 and 0.70 (p
Keywords: peripheral artery disease; lower extremity artery disease; percutaneous transluminal angioplasty